2009
DOI: 10.1007/s11130-009-0123-2
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Radical Scavenging Capacity of Berries and Related Jams from Certificated Area in Serbia

Abstract: Chemical composition and the effects of domestic processing and storage were studied in organically cultivated or wild growing berries, harvested in certificated area in Serbia. The total phenolics content in fresh berries ranged from 380 to 1660 mg GAE/100 g. The phenolic content decreased during the processing to jams, and storage in almost all samples, except in black currant. Among fresh berries, the highest amount of total anthocyanins was found in bilberry (0.61 +/- 0.03 %). Processing and storage caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 18 publications
(34 reference statements)
9
41
2
1
Order By: Relevance
“…Furthermore, there are also some studies which have reported an antioxidant effect in vitro, but not in vivo [41]. Moreover, the strawberry variant and temperature conditions are also important factors in the loss of antioxidants content [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are also some studies which have reported an antioxidant effect in vitro, but not in vivo [41]. Moreover, the strawberry variant and temperature conditions are also important factors in the loss of antioxidants content [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Nicoli et al (1999), food processing may affect the content, activity and bioavailability of these compounds, since they may be degraded or leached into cooking water. Savikin et al (2009) reported that the processing of different fruits into jam causes a reduction in the total phenolic compounds, anthocyanin, and antioxidant activity.…”
Section: Bioactive Compounds and Antioxidant Activitymentioning
confidence: 99%
“…With a low energy value, they are abundant in vitamin C, polyphenols and organic acids (de Ancos et al, 1999;Šavikin et al, 2009). In view of their seasonal availability and low level of stability, such fruits should undergo processing after harvest, making them available for consumption throughout the year.…”
Section: Introductionmentioning
confidence: 99%